The Competencies of the Islamic Primary Madrasah Student Teachers in Developing K 13-Based Lesson Plan in Aceh - Misbahul Jannah; Jarjani Usman (AT-TA'LIM, 2019)
This study aims to examine the extent to which the Pendidikan Guru Madrasah Ibtidaiyah (PGMI) or Islamic primary madrasah student teachers have been competent in developing K13-based lesson plan. 34 students studying at PGMI Department of the Faculty of Education and Teacher Training of a state Islamic university participated in this study. This research employed qualitative descriptive method. The results show that in general the ability of the student teachers in developing K13-based lesson plan fall into less and good categories. This indicates that the ability of the student teachers has not fully met the process standards of the 2007 regulation no 41 by Ministry of Education and Culture (MOEC). This suggests that the PGMI program make sure that every PGMI student teacher have adequate competencies of developing lesson plan based on K-13 based on the currently implemented approach, such as the scientific approach, and using it in their teaching well.